The electronic counting arm movement test (eCAM test). (1st June 2015) - Bodranghien, Florian; Martin, Claire; Ansay, Caroline; Camut, Stephane; Busegnies, Yves; Manto, Mario
<x content-type="archive" xml:space="preserve">Abstract</x> A novel transportable electronic platform aiming to characterize the performance of successive fast vertical visually guided pointing movements toward two fixed targets (eCAM test: electronic counting arm movement test) is described and one validation test is presented. This platform is based on an Arduino® micro-controller and a Processing® routine. It records both the pointing performance (number of clicks) and the elapsed time between two successive pointing movements. Using this novel platform, we studied the effects of functional electrical stimulation (FES) applied on the dominant upper limb in 15 healthy volunteers (mean age ± SD: 22·3 ± 4·3 years; 5 males/10 females). The following muscles were stimulated: flexor carpi radialis (FCR), extensor carpi radialis (ECR), biceps brachii (BB), and triceps brachii (TB). The intensities of the stimulation were 2 and 3 mA above the sensory threshold (ST). Movement times were lesser when performed against gravity and pointing performance improved with FES. We provide the first demonstration that low-intensity FES impacts on motor performances during successive vertical goal-directed pointing movements under visual guidance. The eCAM test is currently the sole electronic tool to assess quickly and easily the performances of successive vertical pointing movements. Future potential applications include, in particular, the follow-up of the effects of neurorehabilitation of neurological/neurosurgical disorders associated with hand–eye incoordination, the functional evaluation of upper limb prosthesis or orthosis, and the analysis of the effects of FES in central or peripheral nervous system disorders.